".The position of Taha Hussein towards the Prophecy of Prophet Mohammad – peace and blessings upon Him – and the revelation in his book named "Pre- Islamic Poetry - Al-Dameg, Huda bint Abdullah (Journal of Islamic Sciences, 2018)
The idea of the study: That to infer the position of Taha Hussein towards the Prophecy of Prophet Mohammad – peace and blessings upon Him – and revelation which has been brought, through the presentation of his statements and views about these two matters contained his book "Pre- Islamic Poetry" and discuss this under the light of the Islamic Faith and the methodology of Al Sunnah and Al Jama'aThe study findings:1- The approach of Taha Hussein in his book "Pre- Islamic Poetry" was characterized by the method of suspicion, raising similarities and exciting suspicion about the constants and undeniable issues.2- In the conception of Taha Hussein; that Prophet – peace and blessings upon Him – is only an ordinary man, aspiring to have political authority and economic power, in fact, there is no prophecy and there He has no message.3- Taha Hussein considers the source of Holey Quran has been made by the Prophet – peace and blessings upon Him – as He has been influenced by the environment affects around, it is not a revelation and ALLAH has not reveal the Holey Quran and not deemed to be a miracle.4- The provision of the Holy Quran in the written material of Taha Hussein has a limited value, time and space.
Keywords: doctrine; revelation; Prophecy; Taha Hussein; stochastic deviations